Blessed Rage for Order: The New Pluralism in Theology - John B Chethimattam (Journal of Dharma, 1977)
In place of the "perennial" philosophy of Aristotle-and the Church recognized and recommended Scholastic Theology-today, we are faced with a plurality of theologies, not to speak of the multitude of new philosophical schools they assume for their basis. Some are baffled and confused by this Babel of tongues among those who try to build the tower of faith. But David Tracy in the book under review starts with the assumption that the present pluralism is a good thing allowing each theologian "to learn in- comparably more about reality by disclosing really different ways of viewing both our common humanity and Christianity" provided each one attempts to articulate and defend an explicit method of inquiry. The present world is disenchanted with mystification both from the Church authorities and from secular thinkers. The con- temporary theologian, ethically committed to the discipline of scientific thought, is forced "to assume a critical posture towards his own and his tradition's beliefs" (p. 7) in order to attain a self-understanding of that tradition. The book is quite impressive because of the thorough knowledge the author shows concerning contemporary theological literature in the West, both Catholic and Protestant.